4(x-5)=2(x+3

Simple and best practice solution for 4(x-5)=2(x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-5)=2(x+3 equation:



4(x-5)=2(x+3
We move all terms to the left:
4(x-5)-(2(x+3)=0
We multiply parentheses
4x-(2(x+3)-20=0

See similar equations:

| 10y=15/13 | | 4)-11=-y+6 | | x+17=19-x | | x–18=27 | | 4f+f+6f=0 | | √5x+4=2x+2 | | 3)n/10-9=-10 | | 15x=−9/13 | | 5x=5-30x | | X-7-4x=0 | | (9x-6)/(x-2)=12 | | 2n+5+3n=0 | | 5x/1-6x=5 | | 2)9=b-(-2) | | 2x-14=5x+2 | | 2x-14=5x+3 | | 3x+2/1-(3x.2)=5 | | 500=45x-85 | | x4+x3−13x2−x+12=0 | | 14-5x=-5x-1 | | 3x+2/1-3x.2=5 | | 3x+2=1-3x.2=5 | | 1)-r/4=-10 | | 3x+2=1-3x.2 | | 6(7X+5)-4(9-8x)=364 | | 4(2k+8)=8 | | 4^(2k+8)=24 | | 3*4(2k-8)=24 | | 3^3x-24=27 | | 4n^2+11n+5=0 | | 3d+7=2d−(3+3d) | | 4(n-3)=5(n+6) |

Equations solver categories